The effect of using the Jigsaw cooperative learning strategy in learning the lateral wheel skill of ground movements in gymnastics Dr. Bilal Mahmoud* Dr. Maher Nasr** Ola Brebdane - محمود بلال; نصر ماهر; بريبداني علا (Latakia University Journal -Medical Sciences Series, 2021)
This study aimed to study the effect of using Jigsaw cooperative learning strategy on learning the lateral wheel skill of ground movements in gymnastics. The experimental approach was used as a general method for research, and the research community consisted of second year students of the Faculty of Physical Education at Tishreen University in the first semester 2019 / 2020 AD. After designing the educational program, it was applied to a sample of (21) students. The results were as follows: The use of the Jigsaw strategy has a positive effect in learning the lateral wheel skill of ground movements in gymnastics. The research recommends subsequent studies on different sports and various strategies.